2015
DOI: 10.1186/s12900-015-0048-y
|View full text |Cite
|
Sign up to set email alerts
|

The origin of β-strand bending in globular proteins

Abstract: BackgroundMany β-strands are not flat but bend and/or twist. However, although almost all β-strands have a twist, not all have a bend, suggesting that the underlying force(s) driving β-strand bending is distinct from that for the twist. We, therefore, investigated the physical origin(s) of β-strand bends.MethodsWe calculated rotation, twist and bend angles for a four-residue short frame. Fixed-length fragments consisting of six residues found in three consecutive short frames were used to evaluate the twist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The positive or negative sign of the local bend angle is the sign of the scalar product between the cross product trueLM×trueMN and the perpendicular vector trueRCα()i+1 . The distributions of local bend angles were normalized by the following equation to account for differences in the number of cases of each angle, which is proportional to the circumference of the circle of radius sin| θ | N=Nsin()||normalθbend …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive or negative sign of the local bend angle is the sign of the scalar product between the cross product trueLM×trueMN and the perpendicular vector trueRCα()i+1 . The distributions of local bend angles were normalized by the following equation to account for differences in the number of cases of each angle, which is proportional to the circumference of the circle of radius sin| θ | N=Nsin()||normalθbend …”
Section: Methodsmentioning
confidence: 99%
“…We concluded that the side chains of these residues influence the relative strength of inter‐strand hydrogen bonds, thereby suppressing β‐strand twisting and bending for WS proteins. Furthermore, we investigated the origin of β‐strand bending for WS proteins and found that the main driving force for full‐length β‐strand bending is hydrophobic interactions involving aromatic residues, whereas that for local β‐strand bending is hydrophobic interactions involving aliphatic residues …”
Section: Introductionmentioning
confidence: 99%
“…1B). We relied on sidechain packing to drive strand bending in strands without β-bulges (see ref (26) and fig. S5).…”
mentioning
confidence: 99%
“…The destabilizing effect of V228 is not surprising. Indeed, from the propensity of the different amino-acids for a-helix or b-strand, 47 Valine does not favor a-helix formation. Furthermore, in M228V CpxA, two successive Valines are located at the positions 228 and 229, and molecular dynamics trajectories recorded on an a helix containing two successive Valines have shown 48 a larger drift of the a carbon coordinates and a decrease of the hydrogen bonds formation.…”
Section: Discussionmentioning
confidence: 99%